Integrating Islamic Religious Education for SDGs: A Systematic Literature Review and Bibliometric Study - Burhan Efendi; Happy Susanto; Nuraini; Mokmin Bin Basri; Muh Samsuri (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to systematically examine the development of interdisciplinary integration of Islamic Religious Education (IRE) and its contribution to the achievement of the SDGs, especially SDG 4 (quality education), SDG 16 (peace and justice), and SDG 13 (environmental responsibility). Theoretical framework: The theoretical framework refers to the integration of IRE in three main domains: epistemological-philosophical, pedagogical-practical, and institutional-structural, and is associated with the values of sustainable development. Literature review: Previous studies have addressed the integration of Islamic values into science, moderate curriculum, character education, and digital transformation, with the main contributions coming from Indonesia and Malaysia since 2019. Methods: The study used the Systematic Literature Review (SLR) approach based on the PRISMA protocol, as well as bibliometric analysis using VOSviewer. Of the 2,083 articles in Scopus, 25 passed the selection. Results: An increase in publications related to IRE integration has been found since 2019. There are eight key indicators of integration classified into the three conceptual domains above. Implications: The results of this study offer a conceptual and practical framework for the development of an IRE curriculum that is adaptive to social and global issues and relevant in supporting the SDGs agenda. Novelty: This study uniquely combines SLR and bibliometric approaches and identifies new classifications of IRE integration practices that are directly associated with the three main SDGs targets.